2014
DOI: 10.3109/0886022x.2014.934177
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD2-associated protein in podocyte apoptosis and proteinuria induced by angiotensin II

Abstract: Podocytes are highly differentiated epithelial cells that form interdigitating foot processes with bridging slit diaphragms (SDs) that regulate renal ultrafiltration. Proteinuria is the most common clinical manifestation of glomerular diseases. Losartan is the traditional reninangiotensin system (RAS). However; the precise mechanisms underlying the beneficial effects of Losartan on podocytes are still unknown. This study tested the hypothesis that podocytes were exposed to Angiotensin II (Ang II) to induce apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The apoptosis assays performed on podocytes under HG and ANG II treatments also reinforced observations previously confirmed by other authors ( 16 , 19 , 20 ). Complementing these results, morphological analyses of treated podocytes showed an increase in apoptosis characteristic features in cells exposed to both treatments.…”
Section: Discussionsupporting
confidence: 89%
“…The apoptosis assays performed on podocytes under HG and ANG II treatments also reinforced observations previously confirmed by other authors ( 16 , 19 , 20 ). Complementing these results, morphological analyses of treated podocytes showed an increase in apoptosis characteristic features in cells exposed to both treatments.…”
Section: Discussionsupporting
confidence: 89%
“…These results demonstrated that MiR-30a may regulate cardiomyocyte autophagy through Beclin-1, during injury induced by Ang II. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that MiR-30a may regulate cardiomyocyte autophagy through Beclin-1, during injury induced by Ang II. 23,24 Our rat study results demonstrated that MiR-30a plays an important role by regulating the Beclin-1 protein during Ang II damage, so it became possible to control the autophagy under a beneficial threshold by regulating MiR-30a expression, to protect cardiomyocytes against injury induced by Ang II. The ratio of Beclin-1/LC3-I in different groups: It was found that Beclin-1 was up-regulated by IR (n = 10 each, p = 0 < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…2 Anesthetic agents administered can cause apoptosismediated neurodegeneration and synapse loss, whereas they increase synaptogenesis later in neurodevelopment. [3][4][5] Recent studies based on rodents had demonstrated that maternal anesthesia in the second trimester pregnancy for several hours can induce neurodegeneration of the fetal rats. In the second trimester of pregnancy, both the rodent and human fetus show similar neurodevelopmental profiles.…”
Section: Introductionmentioning
confidence: 99%